Answer:
x=0 and y=6
Explanation:
First, you would solve x=y-6 for x.
x=y-6 so you substitute the x in -6x-2y=-12 with (y-6)
-6x-2y=-12 → -6(y-6)-2y=-12
Simplify both sides of the equation = -8y+36=-12
Add -36 to both sides to remove it = -8y+36+-36=-12+-36
-8y+36+-36=-12+-36 → -8y=-48
Divide both sides by -8 to remove it.
→ y=6
I believe where you went wrong was with where you substituted y-6.
y-6 is the substitute for x so in parenthesis you would put (y-6) where x is in -6x-2y=-12 making the new equation -6(y-6)-2y=-12.